Sackett's land - L'Amour, Louis, 1908-1988 (L'Amour, Louis, 1908-1988. Sacketts., 1975)
This is the first half of the story of Barnabus, the patriarch of the Sackett clan, and his migration to North America in 1600. His saga begins when he discovers a purse of gold coins in the mud of Devil's Dyke in Finland. On the run from English authorities, he meets and marries Abigail Tempany, the daughter of a sea captain. Nick Bardle, the master of a merchant vessel, the Jolly Jack, is half pirate, ready to take any advantage of any activity promising a profit. He shanghais Barnabus, intending to lose him overboard somewhere en route to the Indies. Barnabus proves too good a seaman to waste, and his murder is delayed too long. He and others escape and travel inland.